Evaluasi Tingkat Kecenderungan Penerapan Tema/Konsep Arsitektur Nusantara Dalam Skripsi Arsitektur Tahun Akademik 2007-2011 - Handajani, Rinawati P.; Asikin, Damayanti; Pamungkas, Sigmawan T.; Nugroho, Agung Murti; Astrini, Wulan (RUAS (Review of Urbanism and Architectural Studies), 2012)
This study aimed to determine the level of student tendencies in the Department of Architecture FTUB in impelementing Nusantara Architecture in their final task and to knwo the variety of Nusantara Architecture concept that have been implemented by graduates of Department of Architecture FTUB. The limitation of this study is the final task of students of Department of Architecture FTUB within the last 5 years (2007-2011). Evaluation indicators are tendency level of implementing Nusantara Architecture theme/concept which is confined to the theme, isue, approaches and outcomes. Benefits provided from this study, especially for Department of Architecture FTUB are to evaluate the success of the curriculum to enhance competency in accordance with the vision and mission of the department, as a guide for the improvement and development of curriculum-based Nusantara Architecture, as a guide in the development of lecturing materials by each laboratory. Besides, it is expected to provide benefits to other departments in the FTUB to evaluate the successful in implementing curriculum to improve the competence of graduates.Keywords: Final task, tendency level, Nusantara Architecture